Influence of fused deposition modeling process parameters on the mechanical properties of PETG parts. (2020) - Srinivasan, R.; Prathap, P.; Raj, Asrith; Aswinth Kannan, S.; Deepak, V.
Abstract: This research work is aimed to provide insight on the dependency of mechanical properties on process parameters of the Fused Deposition Modeling (FDM) printed Polyethylene Terephthalate Glycol (PETG) parts. The experimental investigation is carried out on the PETG material to analyze the individual effect of process parameters such as layer thickness, infill density and infill pattern on the mechanical properties. Specimens were fabricated as per the ASTM standard for the various combination of the above mentioned process parameters. Tensile strength and surface roughness were performed on the Universal testing and surface roughness testing machine respectively. Among the process parameters selected for the fabrication, it is noted that the tensile strength decreases with increase in layer thickness and tensile strength increases with increase in infill density. The infill pattern combined with build orientation produces variations in tensile strength. Surface roughness value decreases with increase in infill density. From the experiment, suitable process parameters for an assuring tensile strength were inspected and studied to establish better end user functional parts.